The Relationship Between Husband Support and Behavior of Pregnant Teenagers to Face Pregnancy During the Covid-19 Pandemic in Gombong, Kebumen, Indonesia - Wulan Rahmadhani; Jipri Suyanto; Than Kyaw Soe; Siti Mutoharoh (Disease Prevention and Public Health Journal, 2021)
Background: Age influences pregnancy and childbirth. Pregnant women aged less than 20 years old or pregnant adolescents are not physically and mentally ready to cope with pregnancy or childbirth. The husband's support highly determines the health status of the mother. This research aimed to determine the relationship between husband support and the behavior of pregnant adolescents to face pregnancy during the COVID-19 pandemic in the Gombong District, Kebumen Regency. Methods: This study used a cross-sectional approach. The population was all pregnant women aged less than 20 years in the Gombong District, Kebumen Regency. It used a saturated sampling technique involving 256 people. Data were analyzed using univariate and bivariate analysis to answer the percentage and the Chi-Square test to answer the research hypothesis. Results: The study showed that 130 (50.8%) husbands did not support the mothers, and 126 (49.2%) husbands supported the mothers. The result also showed that 116 (45.3%) of the pregnant women showed positive behavior, while140 (54.7%) pregnant women showed negative behavior. The chi-square test found a p-value of 0.005, which proved a significant relationship between the husband's support and the behavior of pregnant adolescents to overcome pregnancy during the covid-19 pandemic. Conclusion: Pregnant teenagers with husband support will prepare for pregnancy and childbirth programs more maturely to ensure the safety of both mother and fetus.